Egyptian mythology A to Z a young reader's companion - Remler, Pat. (New York, NY Facts on File, 2000)
Alphabetically arranged definitions present an overview of Egyptian mythology from the Predynastic period through the Roman period.
Includes bibliographical references (p. 175-176) and index.
Keywords: Mythology, Egyptian; Egypt -- Religion -- Encyclopedias